The Chemical Composition of Endotoxin Isolated from Intestinal Strain of Desulfovibrio desulfuricans. (2nd May 2012) - Lodowska, Jolanta; Wolny, Daniel; Jaworska-Kik, Marzena; Kurkiewicz, Sławomir; Dzierżewicz, Zofia; Węglarz, Ludmiła
Abstract : Desulfovibrio desulfuricans anaerobes are constituents of human alimentary tract microflora. There are suggestions that they take part in the pathogenesis of periodontitis and some gastrointestinal inflammatory disorders, such as ulcerative colitis or Crohn's disease. Endotoxin is one of Gram-negative bacteria cellular components that influence these microorganisms pathogenicity. Endotoxin is a lipid-polisaccharide heteropolymer consisting of three elements: lipid A, core oligosaccharide, and O-specific polysaccharide, also called antigen-O. The biological activity of lipopolysaccharide (LPS) is determined by its structure. In this study, we show that rhamnose, fucose, mannose, glucose, galactose, heptose, and 2-keto-3-deoxyoctulosonic acid (Kdo) are constituents of D. desulfuricans endotoxin oligosaccharide core and O-antigen. Lipid A of these bacteria LPS is composed of glucosamine disaccharide substituted by 3-acyloxyacyl residues: ester-bound 3-(dodecanoyloxy)tetradecanoic, 3-(hexadecanoyloxy)tetradecanoic acid, and amide-bound 3-(tetradecanoyloxy)tetradecanoic acid.